4(2m-3)=5m+6+3m+6

Simple and best practice solution for 4(2m-3)=5m+6+3m+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2m-3)=5m+6+3m+6 equation:


Simplifying
4(2m + -3) = 5m + 6 + 3m + 6

Reorder the terms:
4(-3 + 2m) = 5m + 6 + 3m + 6
(-3 * 4 + 2m * 4) = 5m + 6 + 3m + 6
(-12 + 8m) = 5m + 6 + 3m + 6

Reorder the terms:
-12 + 8m = 6 + 6 + 5m + 3m

Combine like terms: 6 + 6 = 12
-12 + 8m = 12 + 5m + 3m

Combine like terms: 5m + 3m = 8m
-12 + 8m = 12 + 8m

Add '-8m' to each side of the equation.
-12 + 8m + -8m = 12 + 8m + -8m

Combine like terms: 8m + -8m = 0
-12 + 0 = 12 + 8m + -8m
-12 = 12 + 8m + -8m

Combine like terms: 8m + -8m = 0
-12 = 12 + 0
-12 = 12

Solving
-12 = 12

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 2x^4-2x^3+3x^2+2x-2=0 | | 18+49m=74 | | 3x^3-5x^2+10x+9=2 | | 2(x+3)=-4x-30 | | 3x^3-5x^2+10x+9=5 | | (-11+2i)-(7-8i)=0 | | 11+19= | | 15x-16=14x | | -9(12-12x)=-9(12+5x)+3x | | -5x+17=-33x | | 14+4x=43 | | 12x+5y+7y-3x= | | 5x-22=2x-4 | | -35x-7y=56 | | 2x-6+5x+3=46 | | A(3x+8)=-18x+b | | 40x=41x-2 | | 3x+17=4x | | -c=-22 | | 3+1=4x+1 | | 3x^3-5x^2+10x+9= | | q-11=9 | | 33x+-4=95 | | 3+1=7y+2 | | 2w+3-4w=17-(3w+2) | | 3+1=7y-2 | | 3=-12c+7 | | 3+1=7y-9 | | 15t-11t= | | 3=-15/2 | | 4x+4+4x=2(4x+2) | | 3/5=f/-5 |

Equations solver categories